Māori Values and Perspectives to Inform Collaborative Processes and Planning for Freshwater Management. Landcare Research contract Report No. LC2119. 66p. - Robb, Mahuru; Harmsworth, Garth; Awatere, Shaun (2015)
This report was written in response to the new freshwater reforms and VMO research objectives. The initial research question to be answered was: What is the role of cultural monitoring to inform the collaborative process? This research question was broadened to “provide Māori values and perspectives that inform collaborative processes and planning for freshwater management”, and includes a section on the role of cultural monitoring in collaborative processes. Key objectives were: • Document the Māori historical and legislative context for the collaborative process, including the role of the Treaty of Waitangi • Collate case study information from around New Zealand, on co-governance, co-management and co-planning and define these terms • Provide a range of useful tools to support successful collaboration by Māori and councils in collaborative freshwater management • Identify future challenges.
Keywords: co-governance; tiriti o waitangi/treaty of waitangi; water management